Physical activities in the wheelchair and out : an illustrated guide to personalizing participation - Davis, E. Ann. (Unites States of America : Human Kinetcs, 2012)
In this book, you will find ideas that provide opportunities for individuals with disabilities to develop basic participation skills in ways that meet their unique ability.
Chapter1. body Awareness -- Chapter2. Drop -- Chapter3. Push -- Chapter4. Toss -- Chapter5. Throw -- Chapter6. Kick -- Chapter7. Catch -- Chapter8. Strike -- Chapter9. Odds and Ends -- Chapter10. Games .
Keywords: ACTIVITY PROGRAMS IN EDUCATION